Compartment-Specific Biosensors Reveal a Complementary Subcellular Distribution of Bioactive Furin and PC7 - Pierpaolo Ginefra; Bruno G.H. Filippi; Prudence Donovan; Sylvain Bessonnard; Daniel B. Constam (Cell Reports, 2018)
Summary: Furin trafficking, and that of related proprotein convertases (PCs), may regulate which substrates are accessible for endoproteolysis, but tools to directly test this hypothesis have been lacking. Here, we develop targeted biosensors that indicate Furin activity in endosomes is 10-fold less inhibited by decanoyl-RVKR-chloromethylketone and enriched >3-fold in endosomes compared to the trans-Golgi network (TGN). Endogenous PC7, which resists this inhibitor, was active in distinct vesicles. Only overexpressed PC7 activity reached the cell surface, endosomes, and the TGN. A PLC motif in the cytosolic tail of PC7 was dispensable for endosomal activity, but it was specifically required for TGN recycling and to rescue proActivin-A cleavage in Furin-depleted B16F1 melanoma cells. In sharp contrast, PC7 complemented Furin in cleaving Notch1 independently of PLC-mediated TGN access. Our study provides a proof in principle that compartment-specific biosensors can be used to gain insight into the regulation of PC trafficking and to map the tropism of PC-specific inhibitors.